TÜRKİYE'DE MÜLTECİLERE HİZMET VEREN PROFESYONELLERİN İKİNCİL TRAVMATİK STRES DÜZEYİ, PSİKOLOJİK DAYANIKLILIK VE ALGILANAN SOSYAL DESTEKLERİ ARASINDAKİ İLİŞKİNİN İNCELENMESİ. - DURDYYEVA, Guncha; ERBAY, Elif Özge (Journal of International Social Research / Uluslararası Sosyal Araştırmalar Dergisi, 2021)
The purpose of this study is investigating the relationship between secondary traumatic stress level of professionals providing services to refugees in Turkey, their psychological resilience and perceived social support. For this purpose, 150 professionals who work in Immigration Administration, non-governmental organizations, foundations, and associations which serves refugees in Turkey, were selected randomly and applied secondary traumatic stress scale, psychological resilience scale and perceived social support scale online. The data were analyzed with Statistical Package for Social Sciences (SPSS 22) program. A positive significant relationship was found between psychological resilience and all dimensions of multidimensional stress. A significant negative relationship was also found between secondary traumatic stress, dedication as a dimension of psychological resilience and a special human dimension as a dimension of perceived social support.